The Role of Uzbek Folk Music Genres in Educating Young People - Mavlyuda Karimova (Researchparks Publishing, 2021)
Folk music is one of the powerful means of education that serves to develop a person artistically and aesthetically. Therefore, folk music as a means of national education - spiritual and aesthetic ideas help our youth to form and develop high human qualities such as patriotism, mutual assistance, friendship, honesty, truthfulness, nobility.